PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN DI RESTORAN YORICHI BBQ & SHABU-SHABU DEPOK DI MASA COVID19 - Dewi Kurniawati; Harimurti Wulandjani; Shofana Sekar Humairoh (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2022)
One of the phenomena currently occurring in big cities in the Greater Jakarta area especially is the culinary issue of Shabu-Shabu and Grill with the All You Can Eat (AYCE) concept, where consumers can eat as much as they want for a specified time and only pay a certain price. With the main menu that is generally served is meat - fresh meat. This study aims to determine the effect of service, product quality and price on customer satisfaction at Yorichi BBQ and Shabu-shabu Depok restaurants. This research is quantitative with descriptive method. The sample of this study amounted to 80 respondents. Method of data analysis using multiple linear regression coefficient of determination. The results showed that: (1) service quality variables partially significant effect on customer satisfaction Yorichi; (2) The product quality variable has a partially significant effect on Yorichi customer satisfaction; (3) The price variable has a partially significant effect on Yorichi customer satisfaction; (4) The variables service quality, product quality and price simultaneously have a significant effect on Yorichi customer satisfaction; (5) Yorichi customer satisfaction is dominated by service quality, product quality, and price by 65.6%. While the rest is 34.4%, except for variables outside the model under study.